Cities in recession : critical responses to the Urban policies of the new right / edited by Ivan Szelenyi - Szelenyi, Ivan (ed.) (London, 1984)
This timely book presents a critical response to the urban policies that are currently being pursued by conservative administrations in Europe and America. The contributors provide a unique transatlantic view of cities in recession, and examine the impact that the urban policies of the New Right are having in such crucial areas as housing, transport, local government, finance and industry. The alternative socialist policies that have emerged in response to urban austerity are fully analysed, and the book points the way to a new approach to urban policy reflecting the changing needs of urban communities.
Keywords: Cities and Towns